Wacana Semiotik di Laman Blog: Kajian Kes ke Atas Sabahkini.net - Syahruddin Ag Ahmad; Nik Norma Nik Hassan; Adnan Hussein (Penerbit UM, 2011)
Semiotic discourse (Idris Aman, 2008) is part of discourse process used to deliver a message on such an issue. Semiotic discourse consists of photographs, graphic illustrations, symbols and icons as it can be accessed visually by the audience of the particular blog site. Graphic illustrations featured in Sabahkini.net purposely displayed to portray local political issues, personalities and also political party through particular ‘sign'(s). An audience's understanding of the issues discussed via blog tested through the display of sign woven in the photograph accompanying the article. Blogger put the visual material to increase understanding on the issue of blog visitors or is likely to present issues in a joke. Hence, the blog site visitors will be graphically stimulated to share their views and arguments on such an issue.